Pandangan Khitan Anak Laki-Laki dalam Hukum Islam dan Tradisi : Analisis Persefektif Keagamaan, Sosial dan Budaya - Misalia Sari; Husnilawati Erlina; Umi Hijriyah; Bambang Irfani (Bulletin of Community Engagement, 2024)
Circumcision of boys is a practice that has a strong religious basis in Islam and is seen as part of human nature. However, the practice and understanding of circumcision varies across Muslim regions, influenced by local traditions that often add cultural elements to the circumcision process. However, there are still challenges in exploring the rights of boys related to the practice of circumcision from the perspective of Islamic tradition and law. This study examines the legal basis of circumcision in Islam and how tradition influences this practice in various Muslim societies. The background is circumcision of boys in Islamic law and tradition. The purpose of this study is to determine the Islamic legal view on circumcision of boys, explore the role of tradition, and analyze its impact on the rights of boys. This research method uses qualitative through literature studies and cultural analysis, this article also discusses how views on circumcision interact with human rights norms, especially regarding the rights of boys. The results of this study indicate that circumcision of boys from the perspective of Islam and Tradition.